The Forecasting Analysis of Profit on Astra Companies List on Indonesia Stock Exchange (IDX) - Sinta Fatmaria Tantri; Nurafni Eltivia; Nur Indah Riwajanti (PT. EQUATOR SINAR AKADEMIA, 2023)
This research aims to analyze the profit forecasting using the weighted moving average method then compare the pattern between Astra companies listed on IDX (Indonesia Stock Exchange). The research method use is quantitative descriptive with secondary data of profit in the 2018-2022 period that provides quarterly. The result for this research shows the highest forecasting of profit on PT Astra International Tbk occurring in the third quarter in 2023 with the amount of 20,970. While the lowest forecasting occurred in first quarter in 2023 with the amount of 9,410. While the lowest forecasting occurred in first quarter in 2023 with the amount of 13,529. The highest forecasting of profit on PT United Tractors Tbk occurs in the third quarter in 2023 with the amount of 13,738,446. While the lowest forecasting occurred in first quarter in 2024 with the amount of 5,584,042. and the highest forecasting of profit on PT United Tractors Tbk occurs in the second quarter in 2023 with the amount of 50,707. While the lowest forecasting occurred in the third quarter in 2024 with the amount of 22,496.